526. Clinical Presenting Characteristics of Pediatric COVID-19 Infection in a Tertiary Care Children's Hospital in Detroit. (31st December 2020) - Ang, Jocelyn Y; Kannikeswaran, Nirupama; Asmar, Basim
Abstract: Background: There is limited data regarding the presenting clinical characteristics of COVID-19 in children. Our objective is to describe the clinical presentations and outcomes of COVID-19 infection early in the pandemic at our institution. Methods: We performed a retrospective chart review of children up to 18 years who underwent testing for SARS CoV-2 from March 1 st to May 10 th 2020 at our pediatric emergency department. We abstracted patient's demographics, clinical presentation, diagnostic studies and patient disposition. We classified the severity of clinical illness based on published criteria. We excluded patients diagnosed with Multisystem Inflammatory Syndrome in Children (MIS-C) associated with COVID-19. Results: SARS CoV-2 testing was performed on 481 patients of whom 43 (8.9%) tested positive. Of these, 4 were diagnosed with MIS-C. Data of 39 patients were analyzed. Patients' demographics, co-morbidities, presenting signs and symptoms and disposition are shown in Table 1. Age range was 47 days – 18 years. Infants representing one third (14/39; 35.9%) of our study cohort. There was equal sex distribution. Asthma or obesity was present in 17 (44%). The most common presenting symptoms included fever, cough, shortness of breath and diarrhea. Chest radiograph showed pneumonia in 12 (30.8%) patients. Two thirds (27/39; 69.2%) were asymptomatic or had mild disease; six patients (15.4%) had severe or critical illness (Figure 1). Nineteen (48%) patients were admitted to the general pediatric service. Eleven (28%) were admitted to the Intensive Care Units (ICU). The characteristics, presenting symptoms and interventions performed in the PICU cohort are shown in Table 2. Half of these patients required mechanical ventilation. There was one death in a 3 month old infant unrelated to SARS CoV-2. Majority of the infants required hospitalization (12/14; 85.7%), including 4 to the PICU (one each for non accidental trauma, ingestion, seizure and pneumonia). Table 1. Patient demographics, signs and symptoms of COVID-19 infection in Children Table 2: PICU patients: Characteristics, Interventions and pharmacotherapy Figure 1: Severity of Ill ness in the study cohort Conclusion: Majority (17; 43%) of our children with COVID-19 had a mild disease. Eleven (28%) including 4 infants required critical care; 5 required mechanical ventilation. There was no COVID-19 related mortality. Larger studies are needed to further define the spectrum of COVID- 19 and risk factors associated with severe disease in children. Disclosures: All Authors : No reported disclosures